2019
DOI: 10.2147/ott.s207460
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impact Of <em>Succinate Dehydrogenase</em> Gene (SDH) Mutations In Renal Cell Carcinoma (RCC): A Systematic Review</p>

Abstract: IntroductionRenal cell cancer (RCC) syndrome is linked to Krebs cycle compartments and their coding genes' alterations like succinate dehydrogenase genes (SDHx). Here we present a systematic review of the SDH genes’ mutations and their impact on both RCC diagnosis and prognosis.MethodsThis systematic review includes any study in which tissue samples of RCC are considered in correlation with the SDHx mutations, microsatellite instability (MSI), and protein expression. For this purpose, a systematic search of ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 85 publications
0
12
0
Order By: Relevance
“…Deleterious mutations in any of the four subunits of complex II decrease SDH activity and result in abnormal accumulation of succinate, as observed in complex II-mutated cells in vitro and in the extracellular fluids (plasma, urine, saliva, and feces) of complex II-deficient patients. Complex II mutations, principally affecting SDHB and SDHD subunits, have been associated with various cancers including hereditary paraganglioma and pheochromocytoma (i.e., neuroendocrine tumors of the paraganglionic tissue), gastrointestinal stromal tumors [ 60 ], and renal cell carcinoma [ 61 ]. Therefore, SDH has now been defined as a tumor suppressor and succinate as an oncometabolite [ 62 , 63 ].…”
Section: Effects Of Mutations In the Subunits Of Complexes I And Imentioning
confidence: 99%
“…Deleterious mutations in any of the four subunits of complex II decrease SDH activity and result in abnormal accumulation of succinate, as observed in complex II-mutated cells in vitro and in the extracellular fluids (plasma, urine, saliva, and feces) of complex II-deficient patients. Complex II mutations, principally affecting SDHB and SDHD subunits, have been associated with various cancers including hereditary paraganglioma and pheochromocytoma (i.e., neuroendocrine tumors of the paraganglionic tissue), gastrointestinal stromal tumors [ 60 ], and renal cell carcinoma [ 61 ]. Therefore, SDH has now been defined as a tumor suppressor and succinate as an oncometabolite [ 62 , 63 ].…”
Section: Effects Of Mutations In the Subunits Of Complexes I And Imentioning
confidence: 99%
“…The LoF of SDH occurs by the loss of heterozygosity (LOH) due to the second allele deletion that arrests the succinate- fumarate conversion [ 37 ]. Cellular metabolomics investigations pointed out the specific accumulation of the succinate [ 38 , 39 , 40 , 41 , 42 ] in tumours that carry the LOH for the SDH x mutated genes including renal cell carcinoma, gastrointestinal stromal tumour, pituitary adenomas pancreatic neuroendocrine tumours [ 43 , 44 , 45 , 46 , 47 , 48 ] and PGLs [ 49 ]. The SDH immunohistochemistry (IHC) staining using specific SDHB antibodies has been proposed as test for the screening of SDH x mutations since the loss of SDHB subunit is correlated with any SDHx mutations [ 50 ].…”
Section: Oncometabolites: the Emerging Of A New Paradigmmentioning
confidence: 99%
“…Ajamir et al have performed a systematic review of all the main studies reporting SDH-mutant renal cell carcinoma [ 46 ]. The most commonly mutated gene was SDHB (with 137G>A being the most frequent mutation) and less frequently SDHC (380A>G being the most frequent mutation) and SDHA [ 46 ].…”
Section: Succinate Dehydrogenase (Sdh) and Fumarate Hydratase (Fh)mentioning
confidence: 99%
“…Ajamir et al have performed a systematic review of all the main studies reporting SDH-mutant renal cell carcinoma [ 46 ]. The most commonly mutated gene was SDHB (with 137G>A being the most frequent mutation) and less frequently SDHC (380A>G being the most frequent mutation) and SDHA [ 46 ]. Rare cases of SDH-deficient renal cell cancers are related to alterations of the SDHA gene: Yakirevich et al reported a case of SDH-deficiency RCC, characterized by homozygous deletion of the SDHA gene (9 of the SDHA gene exons were deleted): at immunohistochemical level, the expression of both SDHA and SDHB was lost [ 47 ].…”
Section: Succinate Dehydrogenase (Sdh) and Fumarate Hydratase (Fh)mentioning
confidence: 99%